Лечение резистентного хронического болевого синдрома - Григорьев, С. В.; Перцов, В. И.; Малая, О. А.; Григор'єв, Сергій Володимирович; Перцов, Володимир Іванович; Мала, О. А.; Grigoryev, S. V.; Pertsov, V. I.; Malaya, O. A. (Украинская медицинская стоматологическая академия, 2017)
Резюме. Актуальность поиска новых эффективных методов лечения хронической боли сегодня не вызывает сомнений. Боль устойчивая к нестероидным аналгетикам и габапентинам стимулирует разработку инвазивных способов лечения хронического болевого синдрома. В работе представлено сравнение комбинации диклофенака и габапентина с хронической эпидуральной аналгезией и эпидуральным нейролизисом. Хроническая инфузия локальных аналгетиков показала лучшие результаты, чем пероральная комбинация. 3 кратное введение 30% спирта в эпидуральное пространство показало наилучшие результаты, что подтвердилось отсутствием потребности в аналгетиках и хронической эпидуральной аналгезии. Эпидуральный нейролизис в нашем исследовании продемонстрировал высокий профиль безопасности. Так нарушения двигательных и тазовых функций отсутствовали, что позволило нам рекомендовать этот способ для лечения случаев устойчивого к стандартной пероральной терапии хронического болевого синдрома. Резюме. Актуальність пошуку нових ефективних методів лікування хронічного болю сьогодні не викликає сумнівів. Біль стійка до нестероїдних аналгетиків і габапентина стимулює розробку інвазивних способів лікування хронічного больового синдрому. У роботі представлено порівняння комбінації диклофенаку та габапентина з хронічною епідуральною аналгезією і епідуральним нейролізісом. Хронічна інфузія локальних аналгетиків показала кращі результати, ніж пероральна комбінація. 3 кратне введення 30% спирту в епідуральний простір показало найкращі результати, що підтвердилося відсутністю потреби в аналгетиках і хронічній епідуральній аналгезії. Епідуральний нейролізіс в нашому дослідженні продемонстрував високий профіль безпеки. Так порушення рухових і тазових функцій були відсутні, що дозволило нам рекомендувати цей спосіб для лікування випадків стійкого до стандартної пероральної терапії хронічного больового синдрому. Abstract. At present, we are witnessing an increase of quantity of patients and victims with chronic pain syndrome. The aging of the population, the deterioration of environmental conditions lead to an increase in the number of neglected oncology and degenerative-dystrophic diseases of the musculoskeletal system. The fighting in Ukraine has formed a fairly large and constantly growing contingent of victims who also need modern algological help. Conservative pharmacological methods are not always able to solve this urgent issue of providing assistance to all of the above categories of patients suffering from chronic pain. Usage of various pharmacological agents capable of reversibly damaging the axons Schwann cells in the posterior horns of spinal cord opens up new possibilities in the controlled limitation of afferent impulses from the painful focus. This method of treating pain allows you to achieve sustainable results from 2 months to several years. Purpose. To investigate the possibility of prolonged epidural analgesia and epidural neurolysis for correction of chronic vertebrogenic pain resistant to combination of diclofenac and gabapentin. Object and methods. 19 patients with degenerative, dystrophic, metastatic and compression injures in the thoracic, lumbar spine and bones, including changes in the bones structures of the vertebrae and ribs, protrusion of the intervertebral discs, compression of the dural sac and spinal nerves, severe pain syndrome for more than 1 month. A comparison of the efficacy of oral NSAIDs (diclofenac 75-150 mg/day + gabapentin 900-1200 mg), chronic neuraxial infusion of local anesthetic (bupivacaine 0,125-0,25%), and neurolytic epidural correction of pain syndrome is suggested. The age of the patients was 61.7 ± 2.7 years, 13 of them women, and 6 men. For the stratification and verification of the pain syndrome, an assessment based on the Visual Analog Scale of Pain was used (the score for VAS was more than 4 points) for more than 1 month. The group of patients taking NSAIDs/gabapentin according to standard recommendations was 8 people (n = 8). A group of patients with chronical epidural analgesia — 6, usually after unsatisfactory treatment with NSAIDs (n = 6). The epidural catheter was established according to the standard method of appropriately splanchnotomic innervation (T5-T6) or in T12-L1 and further cranial 3-5 cm. After standard tests and fixation, the catheter was attached to an elastomeric pump with PCA (Medicom, Vogt) 275-350 ml. The epidural catheter was performed in an outpatient setting or in the operating room with aseptic and antiseptic requirements. Continuous infusion of 0.125-0.25% 2-4 ml/hour. For the neurolysis, 30% ethyl alcohol was injected through the epidural catheter (B/Braun) after zone was verified with working solution of lidocaine (1%) (n = 5). The volume of the neurolytic solution is equal to that of the local anesthetic. With insufficient zonal or qualitative analgesic effect of neurolysis, the volume of the neuronal solution increased or reversed to a permanent infusion of bupivacaine. The injection of the neurolytic solution was repeated up to 3 times at intervals of 1-2 days. After achieving a satisfactory analgesic effect, the epidural catheter was removed. Results and discussion. The efficacy of a single neurolysis should be considered insufficient, 80% of patients required the repeated administration of a neurolytics. The previous process of chronic epidural analgesia had a positive effect on the effectiveness of neurolysis. The relief of pain in these patients was more rapid and more severe than in patients without epidural anamnesis. After 2 sessions of neurolysis, 75% of patients underwent a third neurolysis session. Our data differ somewhat from the literature, probably because of the low concentration of ethyl alcohol in the neurolithic solution. However, a low risk of developing epidural postneurolytic fibrosclerotic after normobaric solution of ethyl alcohol, still has indisputable advantages, despite the large number of injections. With a relapse of pain, it is still possible to introduce an epidural catheter and carry out a routine epidural analgesia program, no disorders of pelvic functions and severe motor disorders have been identified. Combination proved to be equivalent in effectiveness to 3 neurolytic procedures. Conclusions. Thus, invasive epidural pain treatment has proven effective in the treatment of nonsteroid and gabapentin-resistant forms of chronic vertebrogenic pain syndrome. The elimination of pain and the need for analgesics after the 3rd stage of neurolisis is accompanied by an indicative lack of conversions to other methods of analgesia. The combination of diclofenac and gabapentin did not show efficacy in this pathology. The safety and high efficiency of a 3-fold epidural neurolysis with 30% ethyl alcohol make it possible to recommend this procedure to patients with chronic resistent vertebrogenic pain.
Лікування резистентного хронічного больового синдрому
Treatment of resistent chronic pain
Keywords: резистентная хроническая боль; нейролизис; хроническая эпидуральная катетеризация; эпидуральная аналгезия; резистентна хронічна біль; нейролізіс; хронічна епідуральна катетеризація; епідуральна аналгезія; resistent chronical pain; neurolisys; chronical epidural cathether; epidural analgesia